Analisis Perbedaan Tingkat Kepuasan Pengguna Shopee Berdasarkan Status Pekerjaan Menggunakan One-Way Anova - Dhea Aulia Trifadilah; Amelia Yunika Putri; Yemima Filadelvia Sinaga; Sunita Dasman (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
Fierce competition in the e-commerce sector requires companies to understand customer satisfaction levels across various market segments. This study aims to analyze differences in Shopee user satisfaction based on employment status, namely students, college students, and employees. A quantitative method with a comparative approach was used. Data were collected through an online questionnaire from 236 respondents who met the study criteria. The analysis was conducted using IBM SPSS Statistics through validity, reliability, and homogeneity tests, as well as a one-way analysis of variance (ANOVA). The results indicate that the research instrument is valid and reliable, and the data meet the assumption of homogeneity. The ANOVA test revealed differences in satisfaction among the groups, with employees tending to be more satisfied than college students and high school students. These findings confirm that user characteristics, as part of market segmentation, influence the evaluation of e-commerce services. Therefore, companies need to tailor their marketing strategies and service quality improvements to the specific characteristics of each segment to optimize customer satisfaction.